2013
DOI: 10.1111/micc.12033
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐Inducible Factor‐1 Is a Determinant of Lobular Structure and Oxygen Consumption in the Liver

Abstract: Our results suggest that constitutive expression of HIF-1α in hepatocytes acts as a determinant of hepatic lobular structure and oxygen consumption by changing mitochondrial contents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(29 reference statements)
0
12
1
Order By: Relevance
“…The importance of HIF transcription factors for structural maintenance of the liver is exemplified in studies from mice with hepatocyte-specific HIF-1α deficiency. Those mice displayed an extension of hepatic lobules, an enhanced lobular oxygen consumption and an increased content of mtDNA [44]. Further, HIFs regulate major metabolic liver functions, and in particular studies in which either ARNT or the two HIFα subunits were deleted supported this.…”
Section: Hypoxia-inducible Transcription Factors (Hifs)mentioning
confidence: 86%
“…The importance of HIF transcription factors for structural maintenance of the liver is exemplified in studies from mice with hepatocyte-specific HIF-1α deficiency. Those mice displayed an extension of hepatic lobules, an enhanced lobular oxygen consumption and an increased content of mtDNA [44]. Further, HIFs regulate major metabolic liver functions, and in particular studies in which either ARNT or the two HIFα subunits were deleted supported this.…”
Section: Hypoxia-inducible Transcription Factors (Hifs)mentioning
confidence: 86%
“…HIF-1α is degraded under normal oxygen stress and undergoes ubiquitination. However, degradation is suppressed when the cells are exposed to hypoxic condition; as a result, HIF-1α is amplified rapidly and accumulates in cells [25]. …”
Section: Discussionmentioning
confidence: 99%
“…HIF1α could upregulate expressions of Nanog and Oct4 and is implicated in regulating mitochondrial functions and to promote a metabolic shift toward glycolysis in ESCs and iPSCs . Furthermore, HIF1α is also implicated in suppression of PGC1α expression in different cellular contexts . Therefore, we tested HIF1α protein expression in PKCλ/ιKD ESCs.…”
Section: Resultsmentioning
confidence: 99%
“…The other interesting aspect of this study is direct transcriptional regulation of PGC1α by HIF1α. Several previous studies have shown that, depending on a cellular context, hypoxia could modulate PGC1α expression both in a positive and a negative fashion. However, PGC1α induction by hypoxia does not require HIF1α activity .…”
Section: Discussionmentioning
confidence: 99%